The relationship between organizational culture knowledge management among staff at Universiti Malaysia, Terengganu / Ros Habiba Ramli - Ramli, Ros Habiba (2015)
Perceived organizational culture of an enterprise as one of the main factors supporting implementation and realization of knowledge management was the basis of elaborating this issue in the article. An attempt to determine cultural conditioning of knowledge management was taken. A starting point to description of organizational culture supporting knowledge management was an overview of literature of the subject from the point of view of features of this culture. It allowed selecting several types of characteristics creating convenient, for knowledge management, cultural environment. These characteristics reflecting determined patterns of thinking and behaving were next identified as cultural values. These are: focus on group culture, developmental culture, hierarchy culture and market culture. Strengthening or promoting of selected cultural values would favors knowledge management. There are five dimensions of knowledge management that will be effect on the presences of organizational culture in organization; creating knowledge, capturing knowledge, organizing knowledge, disseminating knowledge and applying knowledge. Formulated in summary on this basis suggestions may serve as practical hints in relation to directions of improving organizational culture of enterprise appropriate to needs of knowledge management.